Handgrip strength in type 2 diabetics and nondiabetics: A comparative cross-sectional study among adults in rural Mysore - Deepak ANIL; M. RAKESH; Shabeena AKBAR; Vijaylakshmi Rao VADAGA; D. Sunil KUMAR (Wolters Kluwer Medknow Publications, 2024)
Objectives: The objective of this study is to assess the handgrip strength (HGS) in patients with type 2 diabetes, compare it with nondiabetes age-matched individuals, and assess the correlation between diabetic status and HGS among diabetic patients. Materials and Methods: A community-based cross-sectional study was conducted in rural Mysore, India, for 4 months. Fifty-eight clinically diagnosed type 2 diabetics and 58 nondiabetics participated in the study. The handheld dynamometer was used to test the HGS of all subjects in their dominant hand. Independent t-test was used to analyze the differences in HGS between patients with and without diabetes. Results: The mean dynamometer reading among diabetics was 19.08 ± 7.51, whereas that in nondiabetics was 27.474 ± 13.11. There was a significant difference in HGSs between diabetics and nondiabetics (P < 0.01). Conclusion: Decreased muscle strength and quality in the upper extremities are associated with type 2 diabetes and can lead to functional and physical limitations. Diabetic patients' HGS should be evaluated promptly to identify any disabilities and plan for appropriate therapy.